Multiple Perspective Analysis pada Penanganan Kejadian Luar Biasa Campak di Kabupaten Sumenep: Analisis Tata Kelola Kesehatan Daerah dan Alternatif Kebijakan - Laras Lingganingrum; Yuni Khofifah Endar Parawangsa; Nada Nafira Almanzani; Bima Dwi Putra Bhayangkara; Dominikus Savio Sasi (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2026)
The measles outbreak in Sumenep Regency was declared an extraordinary event (KLB) in August 2025, with 2,139 suspected cases and 17 child deaths. This situation highlights significant challenges in the capacity of regional health services, particularly in terms of emergency immunization coverage, which has only reached 91.3%, falling short of the herd immunity threshold of 95%. This study aims to analyze structural weaknesses in local health governance and formulate policy interventions to strengthen health workforce capacity, immunization outreach, and outbreak response in Sumenep’s archipelagic areas. The methods used include Multiple Perspective Analysis (technical, organizational, and personal), followed by forecasting techniques and comparison of policy alternatives. The analysis results indicate that the main problem is governance failure rooted in organizational capacity, as evidenced by the lack of public health personnel for promotive and preventive functions in 77% of Community Health Centers (Puskesmas) in Sumenep, which significantly hampers the distribution of services in the archipelago. Key recommendations include strengthening human resource management through redistribution of personnel, training, and performance-based incentives. This study confirms that structural reform in health human resource governance is a prerequisite for improving public service performance and preventing similar outbreaks in the future.